A Community-Driven Intervention for Prostate Cancer Screening in African Americans - Patel, Kushal (Health Educ Behav, 2012)
The purpose of the study was to assess the impact of an educational intervention on prostate cancer screening behavior and knowledge. Participants were 104 African American men, 45 years and older, who had not been screened for prostate cancer with a prostate-specific antigen and/or digital rectal exam within the past year. All participants received an intervention delivered by trained lay community educators using a prostate cancer educational brochure developed in collaboration with the community, with structured interviews preintervention and 3 months postintervention. The main study outcomes included prostate-specific antigen screening rates during the 3-month interval and knowledge, barriers to screenings, and decisional conflict around screening. Compared with the 46 men who did not get screened, the 58 participants who got screened were more likely to have greater than a high school education, annual household incomes ≥$25,000, and a family history of non-prostate cancer (p < .05). Average knowledge scores increased, and barriers to screening scores decreased, from preintervention to postintervention only for participants who had been screened (p < .05). The results of this study demonstrate the feasibility and efficacy of an academic institution collaborating with the African American community to develop a successful prostate cancer educational intervention, an approach that can be expanded to other cancers and other chronic diseases.